Hardness Removal in Safe Drinking Water via In-house Resin - Mishra, Dr. Rahul (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Carboxylic acid has been developed in-house in Desalination Division, which is capable of removing calcium to the extent of 98.5% in substantially short span of time of 5 min from feed containing calcium as high as 500 ppm and the resin work excellently for streams having pH 4–7. Also, the loaded metal ions can be recovered and resin can be reused. In this regard, experimental studies by varying different process parameters viz., concentration, time, loading, mesh size, elution etc. have been reported in this paper to highlight the basic parameters for resin selection. The study indicates experimentation with basic parameters like variation of concentration, time, mesh size, dose rate and elution for removal of calcium as a case study for hardness removal. The parametric studies for sorption of calcium ion by dry sorbent investigated in batch operation which exhibits substantial sorption (more than 99 %). within 15 min (99.4%)in contact with 18 to 20 ASTM mesh size sorbenthaving resin loading of 1 g/100 mL effluent Elution with1NHCl solution is most suitable (more than 98% elution) which helps in reuse of the sorbent.The above result indicates possibility to use the resin for removal of hardness or polishing of such type of hardness producing metal ions. Keywords: hardness removal, poly (acrylamide carboxylic acid) or PAC, scaling, calcium, resin, effluent, parametric studies